2015
DOI: 10.1021/acs.chemmater.5b01734
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt Oxide Encapsulated in C2N-h2D Network Polymer as a Catalyst for Hydrogen Evolution

Abstract: With cobalt oxides as promising catalysts for hydrogen generation, 2D network polymer-supported cobalt-oxide catalysts with good crystallinity are highly anticipated to enhance catalytic performance. Here we report the fabrication of a 2D nitrogenated network polymerencapsulated cobalt-oxide (Co@C 2 N) catalyst via an in situ solvothermal synthesis. Co@C 2 N exhibits outstanding catalytic activities for hydrogen (H 2 ) generation from the hydrolysis of alkaline sodium borohydride (NaBH 4 ) solutions. The rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
70
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(78 citation statements)
references
References 39 publications
(69 reference statements)
5
70
1
2
Order By: Relevance
“…Earlier reports have shown that the C 2 N monolayer is an excellent candidate for gas separation because of its uniformly distributed subnanometer pores with designable pore sizes . Furthermore, C 2 N has been employed for widespread applications such as single‐atom catalysts, hydrogen evolution reactions (HER), oxygen evolution reaction (OER) catalysts, and water desalination …”
Section: Introductionmentioning
confidence: 99%
“…Earlier reports have shown that the C 2 N monolayer is an excellent candidate for gas separation because of its uniformly distributed subnanometer pores with designable pore sizes . Furthermore, C 2 N has been employed for widespread applications such as single‐atom catalysts, hydrogen evolution reactions (HER), oxygen evolution reaction (OER) catalysts, and water desalination …”
Section: Introductionmentioning
confidence: 99%
“…The methanolysis activation energy ( E a ) was evaluated by measuring the hydrogen‐evolution capability at different temperatures. Figure e shows the temperature‐dependent generation of hydrogen for the b‐CuO NA/CF catalyst from 293 to 308 K. As observed, the HGR increases dramatically at higher temperatures, which should be a result of the accelerated movement of the molecules of AB and methanol, and this leads to an increase in the number of effective collisions that pass the threshold energy barrier . However, the final conversion of AB remains almost constant at high temperatures (>298 K).…”
Section: Figurementioning
confidence: 99%
“…Figure 3e shows the temperature-dependentg eneration of hydrogen for the b-CuO NA/CF catalystf rom 293 to 308 K. As observed, the HGR increases dramaticallyathigher temperatures, which should be ar esult of the accelerated movement of the molecules of AB andm ethanol, and this leads to an increase in the number of effective collisions that pass the threshold energy barrier. [41] However,t he final conversion of AB remains almostc onstant at high temperatures (> 298 K). From the slope of the straight line in Figure 3f,t he value of E a was calculated to be 34.7 kJ mol À1 for the AB methanolysis reaction by using the Arrhenius equation (see the Experimental Sectionf or details).…”
mentioning
confidence: 99%
“…Recently, a holey nitrogenated graphene has been synthesized by a simple wet chemical reaction; this material has a layered two‐dimensional multifunctional carbon nitride C 2 N structure with evenly distributed holes and nitrogen atoms . This has been predicted to be a promising material for He separation, hydrogen evolution, and in the oxygen reduction reaction and CO oxidation reaction . On the other hand, C‐doped carbon nitride systems have been reported for spintronic applications …”
Section: Introductionmentioning
confidence: 99%
“…[37] Recently,aholey nitrogenated graphene has been synthesized by as imple wet chemical reaction;t his material has a layered two-dimensional multifunctional carbon nitride C 2 N structure with evenly distributed holes and nitrogen atoms. [38] This has been predicted to be ap romising material for He separation, [39] hydrogen evolution, [40] and in the oxygen reduction [ Metal-free half-metallicity has been the subject of immense research focus in the field of spintronic devices. By using density functional theoretical (DFT) calculations, atomically thin holey nitrogenated graphene (C 2 N) based systemsa re studied for possible spintronica pplications.F erromagnetism is observed in all the C-doped holey nitrogenatedg raphene.…”
Section: Introductionmentioning
confidence: 99%